EFFECT OF YOKO GERI KEKOMI'S KICK ON BODY BALANCE IN NUMBER KARATE ATHLETES AT CLUB INKANAS GARUT - Nursandi, Ari; Kosasih, Alam Hadi; Sonjaya, Azhar Ramadhana (JUARA : Jurnal Olahraga, 2023)
Balance training when kicking is really needed in the Yoko Geri Kekomi kick for karate athletes. When kicking, athletes who lack body balance will experience falls, so training is needed to improve body balance so that the kick can be done well and does not fall when kicking. Many of the athletes at Club Inkanas Kab. Garut, who fell during training, kicked Yoko Geri Kekomi. The aim of this research was to determine the effect of Yoko Geri Kekomi's kick on body balance in kata numbers of karate athletes at the INKANAS Regency club. Garut. The method used in this research is experimental research. This research uses one type of experimental research, namely preexperimental design with a One Group Pretest-Posttest Design research design. The population that will be used in this research is a total of 60 kumite people using a purposive sampling technique with the sample criteria in this study being 15 athletes who are categorized as cadets and above. The instrument used is multiple single leg-hop with data analysis techniques of normality test, homogeneity test and t test. The results of the descriptive data showed that the pre-test average was 1.51 after being given Yoko Geri Kekomi treatment for 16 meetings, the post-test score was 2.48 so it was known that the increase was 0.97. Furthermore, based on the t-test, the calculated t-value was 21.52. The t-table value with df 14 at the 5% significance level is 0.691. Therefore t-count > t-table (21.52 > 0.691) and the significance value is smaller than 0.05 (0.00 < 0.05) so it can be stated that there is a significant increase in the balance score by being given kick training. Yoko Geri Kekomi for 16 meetings. So it can be concluded that there is a significant difference between before the treatment was given and after the treatment was given in improving the balance of karate athletes at the INKANAS Regency club. Garut.